Does High-Quality Financial Reporting Mitigate the Negative Impact of Global Financial Crises on Firm Performance? Evidence from the United Kingdom - Zhiwei Lin; Yihong Jiang; Qingliang Tang; Xiangjian He (Australasian Accounting, Business and Finance Journal, 2015)
Prior literature has claimed that accounting plays a negative role in a financial crisis. The current study sought to determine whether this effect is dependent on the quality of financial reporting. Specifically, this study examined the impact of the quality of financial reporting (as measured via earnings quality) on liquidity (measured by the bid-ask spread) in the equity market during the 2008–2009 global financial crisis in the United Kingdom. We found, as expected, that market liquidity was much lower during the crisis than prior to the crisis; however, firms with high-quality financial reporting suffered fewer negative effects as a result of the financial crisis. The results were robust after controlling for other influences, such as return volatility, loss making, market value of equity, and other potential endogeneity problems. In addition, adopting alternative models for earnings quality did not alter our inferences. Our results support the notion that high-quality accounting information can reduce information asymmetry and hence enhance investor confidence during a financial crisis. The results suggest that a stable financial reporting system is an important part of that overall economic fabric. Our findings will help build a framework on which an overall financial crisis risk-management strategy can be developed to avoid future crises.
Keywords: Financial crisis; Liquidity; Financial reporting quality; Earnings management